2013
DOI: 10.1186/1471-2164-14-503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of G protein-coupled receptor signaling pathway proteins in marine diatoms using comparative genomics

Abstract: BackgroundThe G protein-coupled receptor (GPCR) signaling pathway plays an essential role in signal transmission and response to external stimuli in mammalian cells. Protein components of this pathway have been characterized in plants and simpler eukaryotes such as yeast, but their presence and role in unicellular photosynthetic eukaryotes have not been determined. We use a comparative genomics approach using whole genome sequences and gene expression libraries of four diatoms (Pseudo-nitzschia multiseries, Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…In the RNA‐seq data, PSNMU‐V1.4_AUG‐EV‐PASAV3_0072880.1, homologous to GPCR3 (Port et al ., 2013), is upregulated, and the inositol phospholipid signalling pathway, which is downstream of GPCRs, also appears to be employed by P. multistriata cells to transduce information (Table S10). GPCRs bind many signalling molecules and our data indicate that they might be involved in the perception of mating cues in diatoms, as has been reported in yeast (Alvaro & Thorner, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In the RNA‐seq data, PSNMU‐V1.4_AUG‐EV‐PASAV3_0072880.1, homologous to GPCR3 (Port et al ., 2013), is upregulated, and the inositol phospholipid signalling pathway, which is downstream of GPCRs, also appears to be employed by P. multistriata cells to transduce information (Table S10). GPCRs bind many signalling molecules and our data indicate that they might be involved in the perception of mating cues in diatoms, as has been reported in yeast (Alvaro & Thorner, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Besides P. tricornutum, two other diatoms also have fully assembled and publicly available genome sequences, namely T. pseudonana (Armbrust et al, 2004) and F. cylindrus (Port et al, 2013). These two species contain four and three RGQ-like proteins, respectively.…”
Section: Rgq1 Belongs To a Small Protein Family Conserved In Heterokontsmentioning
confidence: 99%
“…To date, several diatom genomes have been sequenced, among which two are considered model species, the centricate Thalassiosira pseudonana and the pennate Phaeodactylum tricornutum (Armbrust et al, 2004;Bowler et al, 2008). Other currently sequenced diatom genomes include Fragilariopsis cylindrus and Pseudo-nitzschia multiseries (Port et al, 2013) and Thalassiosira oceanica (Lommer et al, 2012); however, the latter two have not been fully assembled yet. The analysis of these genomes showed that there is a large fraction of diatom-specific genes, that diatoms have acquired genes from a variety of other organisms through horizontal gene transfer, and that often relatively little overlap exists between diatom species (Bowler et al, 2008).…”
mentioning
confidence: 99%
“…Although the importance of GPCR signaling has been repeatedly demonstrated in multicellular eukaryotes, there is much to be discovered in unicellular eukaryotes. Components of GPCR signaling pathways have been identified in the genomes of only four diatoms— Pseudo‐nitzschia multiseries , Thalassiosira pseudonana , Phaeodactylum tricornutum , and Fragilariopsis cylindrus (Port et al )—and the prevalence of GPCR signaling has not yet been examined among dinoflagellates. Moreover, a comprehensive overview of diatom GPCR signaling pathway components and their relationships with the versions found in dinoflagellates is lacking.…”
mentioning
confidence: 99%